Аnalysis of rey behavior in the coal combustion process - Pinchuk S.A. (НТУ "ДП", 2025)
Coal is recognized as a valuable source for the recovery of Rare Earth Elements and Yttrium (REY) – a group comprising the 15 lanthanides (La–Lu) as well as scandium (Sc) and yttrium (Y), which share similar chemical properties. These metals are in high demand across various industrial sectors, including the production of batteries, lightweight alloys, magnets, medical equipment, and electronics. Of particular interest are the so-called critical REY (Nd, Eu, Tb, Dy, Y, Er), which relative abundance may vary depending on the origin and characteristics of a given coal. Traditionally, REY are produced via mining of primary deposits (e.g., monazite, xenotime, bastnaesite). However, such methods often carry high costs and significant environmental risks, leading to increased interest in alternative (secondary) sources, among which coal ash has emerged as particularly important.
Keywords: горіння вугілля; поведінка реї; кам’яне вугілля